Peran Teknologi Informasi dalam Bisnis Halal (Studi Penerapan Teknologi Informasi pada Bisnis Syariah) - Safitri, Inchi; Efendi, Ahmad (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
This study aims to provide information regarding the role of information technology in halal business. Through the use of library research methods, this study has established that information technology is a combination of computer technology, which is responsible for processing and storing information. The development of information and communication technology today greatly influences all aspects of people’s lives, especially in the business world, including sharia business. In the Islamic business practices, it is very important to always acknowledge and surrender all efforts to Allah SWT. by recognizing work as a from of worship, one can maintain sincerity in work. Advances in information technology have an important function in the growth and development of sharia business. This can be seen from the functions of information technology it self, such as marketing communication, market share, and so on. Information technology has a role and is applied in several business, such as halal culinary, halal cosmetic, and halal tourism.